A systematic review of measures assessing mental health professionals' perspectives of recovery. (15th June 2021) - Gyamfi, Naomi; Bhullar, Navjot; Islam, Md Shahidul; Usher, Kim
Abstract: Recovery is internationally recognized as a concept to improve the well‐being of consumers. Compared with the numerous measures assessing consumer perspectives of recovery, only a few measures have been developed to assess Mental Health Professionals' (MHPs) perspectives of recovery to inform practice. The present study aims to systematically review the literature to identify existing measures designed to assess MHPs' perspectives of recovery and evaluate their psychometric properties, and the methodological considerations of the design and use of these measures. We searched literature across eight electronic databases: MEDLINE, Web of Science, PsycINFO, PsyArticles, CINAHL, Scopus, EMBASE, and Google scholar. We identified 2631 articles across all databases. Of these, 40 articles met the inclusion criteria, which comprised 14 original measures assessing mental health recovery and 26 articles reassessing the psychometric properties of the original 14 measures. Our results suggested that while there are existing measures for assessing MHPs' perspectives of recovery, only a few of these measures met standard evaluation criteria for psychometric properties. Specifically, the validation of the identified measures is still in its infancy. For example, the easiness of applying the measures differs among the studies, and only a few of the measures fully involved consumers in the scale development phase. The implication of the findings for future use and development of recovery measures in mental health practice and research are discussed and recommended.